Rosto e intencionalidade: superação ou renovação da fenomenologia? - Maslowski, Adriano André (2017)
This dissertation addresses the philosophical and phenomenological thinking of Emmanuel Levinas. Through a study on the work "Totality and Infinity" the aim is to investigate: "Face and Intentionality: overcoming or renewal of phenomenology?". The research has as problematic to analyze how Levinas proposes an overcoming or renovation on the phenomenological method when it proposes radically the face as a countermovement of the intentionality? And, starting from this uneasiness, what elements will Levinas present to support his proposal of facial phenomenology? The research is based on two foundations that, roughly speaking, complement each other: first, the reading of Levinas of his masters Husserl and Heidegger and, in a second moment, the criticism that Levinas expresses to his masters taking phenomenology to a radicalization. To do so, the research is subdivided into three chapters, that is: 1) Levinas: phenomenology and ontology; 2) Original descent as critical to phenomenology; Phenomenology of the face. Starting from a study of his masters Husserl and Heidegger, Levinas points out that the first meaning is neither giving of meaning, being intentional consciousness, nor understanding of being. This author, by the movement of interiority, presents a critique of phenomenology seeking to show the first/origin movement. In a critique of representation and understanding of being, the author opposes totality by presenting the movement of separation, which must be seen as the first connotation. By fruition, a movement that counterposes intentionality, the author will reaffirm subjectivity in an infinite dimension, that is, before the intentional consciousness of an existence that presents itself through the face, which cannot be objectified, it presents itself in its infinite dimension. Subjectivity thus will enable an openness to externality, that is, otherness. For Levinas, the face presents itself as intentional countermovement being ethical, that is, that the face makes the I (nominative) a self (moi) in the accusative, that is, it deprives it of its sovereignty to constitute it as responsible subjectivity. In this sense, the present reflection presents the Levinasian reading of phenomenology as a renewal of the phenomenology of its masters, that is, it leads to a radicalism. This renewal is presented in the work "Totality and Infinity" as a phenomenology in the appearance, which for Levinas is a phenomenology that calls for an ethical relationship of responsibility for the life of another